Dimensions Of Corporate Crime - T. Riza Zarzani; Ismaidar Ismaidar; Wildan Fahriza (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
corporation is a group of people and/or assets that are organized, whether legal entities or non-legal entities. Corporate crimes that occur in Indonesia are quite an important note in law enforcement in Indonesia. The discussion of corporate crime is very different from crimes that occur in general (as regulated in the Criminal Code). The problem formulation in this research is the dimensions of corporate crime. And the aim of the research based on the problem formulation above is to determine and analyze the dimensions of corporate crime. This research method is analytical descriptive research which is research to describe and analyze existing research and is included in the type of library research which will be presented descriptively. Corporate crime has special characteristics when compared to other types of crime. The general view has at least 2 (two) main characteristics, namely Non Violent (non-violent) and Corrosive effect (damaging moral standards). Corporate crime is essentially an act that is condemned by law. Its existence is an act prohibited by any law. Therefore, the understanding of corporate crime can be divided based on the understanding of corporate crime as organized crime because it involves all aspects and parts of the corporation, as transnational crime because the scope of acts carried out is not only in one country but across countries . As a white collar crime considering that corporations are parties who have an important position and have certain economic power in society.